Respostas
respondido por:
2
x(x-3) = 108
x² - 3x = 108
x² - 3x - 108 = 0
x² - 3x = 108
x² - 3x - 108 = 0
respondido por:
1
Olá!
Deve se aplicar a propriedade distributiva para resolver a equação,
Resolução,
x(x - 3) = 108
x² - 3x - 108 = 0
Usando a fórmula de bhaskara,
∆ = 441
x' = 12
x" = - 9
S = {12 ; - 9}
Abraços!
Deve se aplicar a propriedade distributiva para resolver a equação,
Resolução,
x(x - 3) = 108
x² - 3x - 108 = 0
Usando a fórmula de bhaskara,
∆ = 441
x' = 12
x" = - 9
S = {12 ; - 9}
Abraços!
Mateusalencar015:
Obrigado
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás